Use specifications of ornamental rocks based in accelerated ageing tests (2008)
Dimension stone present deterioration process caused by air pollution and some industrial subtances used for application and maintenance. Loss of brilliance, alterations of original color, changes in the porosity and absortion of original color, changes in the ornamental rocks. The alterability tests amd technological characterization, carried out on base of a systematic sampling in the exploration and mining activities, permit the anticipate knowledge of the rock behaviors against environmental conditions, predicting problems that may affect the potential use and trade possibilities of some types of rocks such dimension stones. Six types of Brazilian granites were submitted to different test suchstatic lixiviation, exposition to sulphurous acid and salt crystallization to simulate the main chemical an physical agents of deteroration in rocks applied in external and internal revetment. The degree of microfacturing and the mineralogical constitution are the most important factors of the alterability. A control of porosity and water absorption parameters showed some differences between the different types of granites tested, establishing differences related to the susceptibility to weathering process.